PENGETAHUAN MNEMONIK GURU DALAM MENINGKATKAN KOSA KATA BAHASA INGGRIS ANAK TAMAN KANAK-KANAK DI GUGUS VI KECAMATAN KOTO TANGAH KOTA PADANG - Wirasti, Rani Indah; Hazizah, Nur (FKDP (Forum Komunikasi Dosen Peneliti), 2020)
This study aims to determine the percentage of mnemonic knowledge of teachers in improving the English vocabulary of kindergarten children in Cluster VI, Koto District, Padang City. This research uses a descriptive quantitative approach. The population in this study were all kindergarten teachers in Cluster VI, Koto Tangah District, Padang City. The technique used is the census technique. The data collection methods and instruments used a questionnaire. Methods of data analysis using quantitative descriptive methods. The results showed that the teacher's Mnemonic knowledge in improving the English vocabulary of Kindergarten-Children in Cluster VI, Koto Tangah District, Padang City was in the good category with a percentage of 64.36%. Mnemonic knowledge of teachers is identified through three sub-variables, namely; Knowledge Subvariable, teacher understanding of mnemonic strategies, Knowledge Subvariable, teacher understanding of mnemonic work processes (memory process), Knowledge Subvariable, understanding, and teacher application of types of mnemonics and how they are applied. The three subvariables are in good category with different percentages.